2010
DOI: 10.1123/ijsnem.20.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Excess Postexercise Oxygen Consumption After Aerobic Exercise Training

Abstract: Literature examining the effects of aerobic exercise training on excess postexercise oxygen consumption (EPOC) is sparse. In this study, 9 male participants (19-32 yr) trained (EX) for 12 wk, and 10 in a control group (CON) maintained normal activity. VO(2max), rectal temperature (T(re)), epinephrine, norepinephrine, free fatty acids (FFA), insulin, glucose, blood lactate (BLA), and EPOC were measured before (PRE) and after (POST) the intervention. EPOC at PRE was measured for 120 min after 30 min of treadmill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
3
12
0
3
Order By: Relevance
“…The difference in these findings might be attributable to the nature of the delivery mechanism found in these forms of supplements. Regardless of delivery mechanism, the results of this study did agree with previous studies, which indicate that oxygen delivery is not considered to be the limiting factor in maximal exercise performance (1,13,18,24,31). All variables observed in the recovery phase (first 2 minutes after exhaustion) showed no significant difference with use of the personal OS and the placebo.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The difference in these findings might be attributable to the nature of the delivery mechanism found in these forms of supplements. Regardless of delivery mechanism, the results of this study did agree with previous studies, which indicate that oxygen delivery is not considered to be the limiting factor in maximal exercise performance (1,13,18,24,31). All variables observed in the recovery phase (first 2 minutes after exhaustion) showed no significant difference with use of the personal OS and the placebo.…”
Section: Discussionsupporting
confidence: 88%
“…Recent work suggests that oxygen delivery is not considered to be the limiting factor in maximal exercise performance, and recovery has not been significantly affected by the breathing of oxygenenriched air (1,13,18,24,31). Also, the use of supplemental oxygen before exercise has not resulted in any significantly different physiological effects documented in recovery, as compared with ambient air (21,22,34).…”
Section: Introductionmentioning
confidence: 99%
“…Second, for the purpose of limiting our analyses to a homogenous group of participants, we excluded all of those showing a VO 2max below the 50 th percentile for their age and sex group-matched normative values. It appears that the magnitude of EPOC is decreased in the trained state after exercise performed at the same absolute intensity [46]. Therefore, in persons with poorer levels of cardiorespiratory fitness, interval walking performed at a Froude number of 0.25 likely contributes to a greater magnitude of EPOC than that seen in the present study.…”
Section: Limitations ▼mentioning
confidence: 39%
“…It should be pointed out that the methods of measuring baseline and EPOC duration have not been consistent among investigations. In some cases, baseline and recovery data have been collected with the participants in the seated position [46,47], whereas in others the participants rested supine [5,18]. The seated rest position was used in this study because we have found it to be comfortable and convenient for both participants and researchers.…”
mentioning
confidence: 99%
“…In fact, full recovery appears within 3-4 min post-exercise, which is a common characteristic. Metabolism remained slightly elevated across all conditions during recovery, indicating that despite the exercise cessation, biochemical processes remain active [30]. This was documented by the elevated rate of high glucose uptake in working muscles during recovery [31].…”
Section: Discussionmentioning
confidence: 88%